2018
DOI: 10.1007/s00572-018-0827-y
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhiza facilitates the accumulation of glycyrrhizin and liquiritin in Glycyrrhiza uralensis under drought stress

Abstract: Liquorice (Glycyrrhiza uralensis) is an important medicinal plant for which there is a huge market demand. It has been reported that arbuscular mycorrhizal (AM) symbiosis and drought stress can stimulate the accumulation of the active ingredients, glycyrrhizin and liquiritin, in liquorice plants, but the potential interactions of AM symbiosis and drought stress remain largely unknown. In the present work, we investigated mycorrhizal effects on plant growth and accumulation of glycyrrhizin and liquiritin in liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 67 publications
5
85
0
Order By: Relevance
“…AM symbiosis can improve plant mineral nutrition, especially P, and regulate the biosynthesis of secondary metabolites to enhance plant resistance [47]. In the current study, AM inoculation markedly improved plant growth and facilitated the accumulations of glycyrrhizin and liquiritin compared with the non-AM plants in sterilized soil, which has been proven in our previous studies [28,30]. However, we observed no significant difference in plant growth, including plant height, plant dry weights, nutrient concentrations, photosynthesis traits, and accumulations of glycyrrhizin and liquiritin between the AM plants in sterilized soil and non-AM plants in unsterilized soil, suggesting that AM symbiosis could take over the role of indigenous soil microbial communities to a certain extent to support plant growth and biosynthesis of secondary metabolites.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…AM symbiosis can improve plant mineral nutrition, especially P, and regulate the biosynthesis of secondary metabolites to enhance plant resistance [47]. In the current study, AM inoculation markedly improved plant growth and facilitated the accumulations of glycyrrhizin and liquiritin compared with the non-AM plants in sterilized soil, which has been proven in our previous studies [28,30]. However, we observed no significant difference in plant growth, including plant height, plant dry weights, nutrient concentrations, photosynthesis traits, and accumulations of glycyrrhizin and liquiritin between the AM plants in sterilized soil and non-AM plants in unsterilized soil, suggesting that AM symbiosis could take over the role of indigenous soil microbial communities to a certain extent to support plant growth and biosynthesis of secondary metabolites.…”
Section: Discussionsupporting
confidence: 75%
“…In this study, plants grown in sterilized soil showed significant reductions in glycyrrhizin and liquiritin concentrations, indicating the importance of soil microorganisms in plant secondary metabolism. Nutrient level, especially those of P, essentially affects the accumulation of glycyrrhizin and liquiritin through direct involvement in the biosynthesis of secondary metabolites, regulation of C:N:P ratios and expression of the related genes [30]. Our results indicated that the non-AM plants grown in unsterilized soil had higher levels of root P and C:N ratios and higher concentrations of glycyrrhizin and liquiritin compared with those in sterilized soil.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations